Comparative analysis of the mechanical properties of the ankle and the sole ligaments - (:unkn) unknown (My University, 2002)
Mechanical behavior of some human ankle ligaments, which mostly undergo injury, was studied comparatively. The effect of sudden strain rate change was also observed by suddenly altering crosshead speed during straining portion of the monotonic loading. Stress-strain curves, modulus of elasticity, strain to fracture values and energy absorbed during failure were measured in the course of conventional tensile tests, and cyclic loading. It was found out that various ligaments and marked regions of the same ligament exhibit diversity in terms of strain to fracture values, absorbed energy, Young's modulus and slopes of the stress-strain curves.
Keywords: Anisotropy; Ligaments; Monotonic and cyclic loading; Sudden strain rate change